Global-Local Seismic Performance Discrepancy in Top-Heavy Adaptive Reuse Buildings on Soft Soil - Yusuf, Nabil Mochammad; Wibowo, Ari; Anggraini, Retno (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2026)
Adaptive reuse of existing high-rise buildings often introduces severe vertical mass irregularities, particularly when functional changes significantly increase live loads. Unlike previous studies that typically isolate the effects of vertical irregularity or soft soil, this research distinctly quantifies the compounded detriment of top-heavy adaptive reuse, specifically on soft soil sites. This study conducts a forensic seismic assessment of a 15-story reinforced concrete frame that was converted from an office to an archive storage facility, where live loads increased from 2.4 kN/m² to 7.18 kN/m² on the upper floors. Using Nonlinear Static Procedures according to ASCE 41-17 with semi-rigid diaphragm modeling, the structural response is evaluated under Site Class SE conditions. The analysis reveals a